2017
DOI: 10.1126/sciadv.aao3920
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected high robustness of electrochemical cross-coupling for a broad range of current density

Abstract: Solvent effect enables electrosynthesis of organic compounds with strong variation of electric current at constant efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 34 publications
1
73
0
5
Order By: Relevance
“…using chemical oxidizers demonstrated that this electrochemical cross-coupling can easily compete with conventional methods. [109] Recent studies have highlighted its robustness, [111] and extended the applicability of this process to the electrochemical synthesis of partially protected non-symmetric biphenols, [112] protected bianiline derivatives [113] (Scheme 34, top), and m-terphenyl-2,2''-diols by twofold CÀCc ross-coupling [114] (Scheme 34, bottom). Thec rosscoupling of phenols with heterocycles was recently described.…”
Section: Anodic Couplings By Càha Ctivationmentioning
confidence: 99%
See 2 more Smart Citations
“…using chemical oxidizers demonstrated that this electrochemical cross-coupling can easily compete with conventional methods. [109] Recent studies have highlighted its robustness, [111] and extended the applicability of this process to the electrochemical synthesis of partially protected non-symmetric biphenols, [112] protected bianiline derivatives [113] (Scheme 34, top), and m-terphenyl-2,2''-diols by twofold CÀCc ross-coupling [114] (Scheme 34, bottom). Thec rosscoupling of phenols with heterocycles was recently described.…”
Section: Anodic Couplings By Càha Ctivationmentioning
confidence: 99%
“…[115] All products can be synthesized on multigram scale.The use of high current densities was established in first experiments,a nd has to be tested for further substrate combinations. [111] …”
Section: Anodic Couplings By Càha Ctivationmentioning
confidence: 99%
See 1 more Smart Citation
“…[165] Dies wird besonders fürN eueinsteiger in der Elektrosynthese von Vorteil sein, da kleinere Abweichungen von den ursprünglichen Vorschriften nicht zu drastisch schlechteren Ergebnissen oder gar zum Nichtgelingen führen. Hierbei sollte das Produkt nicht anfällig füreine Überkonversion der gewünschten Verbindung sein oder das Produkt nur durch beispielsweise Lçsungsmitteleffekte hiervor geschützt sein.…”
Section: Angewandte Chemieunclassified
“…[63] Weiterhin wurde kürzlich bei der Reduktion von mikrobiell produzierter Itaconsäure zu Methylbernsteinsäure gezeigt, [64] dass die elektrochemische Verfahrensweise dem chemischen Prozess überlegen war, der auf der heterogenen Katalyse mit H 2 beruhte.R eduktive elektroorganische Reaktionen, die das Produktportfolio fürE lektrobioraffinerien erweitern kçnnen, schließen z. [69,70] Abbildung 4B zeigt den aktuell vorgestellten Elektrobioraffinerieprozess von Mais zu Drop-in-Kraftstoffadditiven,d er die Kolbe-Reaktion auf mikrobiell produzierte mittellangkettige Carbonsäuren anwendet. [66] Bei der Betrachtung von elektrochemischen Oxidationen ist die Kolbe-Elektrolyse definitiv die bekannteste Reaktion zur Veredelung von Intermediaten.…”
Section: Veredelung Von Intermediaten:elektroorganische Reaktionen Vounclassified